Analisis Efektivitas Insentif Pajak Bumi Dan Bangunan Perdesaan dan Perkotaan (PBB-P2) Pada Penerimaan Pajak Daerah Kota Tangerang Tahun 2018 - 2020 - Cindy Noerfalah Tanjung; Jiwa Pribadi; Ryan Dwi Yanuar (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to discuss the effectiveness of the Rural and Urban Land and Building Tax Incentives (PBB-P2) on Tangerang City Regional Tax Revenue in 2018-2020. The main problem in this study is how the level of effectiveness of the tax incentive activities. Rural and Urban Land and Building Tax (PBB-P2). The basis of tax imposition in PBB-P2 is NJOP (Tax Object Sales Value). NJOP is determined by region and determined by the Minister of Finance. The Tangerang City Government through the Regional Revenue Agency (BAPENDA) continues to strive to increase regional revenues from the Rural and Urban Land and Building Tax sector (PBB-P2). The incentives provided are in the form of exemption, reduction, maturity and elimination of sanctions in the form of fines and delays in paying local taxes. The approach used in this research is a qualitative approach with descriptive research methods. Research results realization continues to reach the target. The problem with this target and realization condition is that there is a decrease in the target again in 2020. The realization in 2020 is less than the realization in 2019 but greater than the realization in 2018.